2012
DOI: 10.1097/inf.0b013e3182443fec
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Clearing Helicobacter pylori on Growth in School-age Children

Abstract: Background A new H. pylori infection affects growth velocity negatively, and clearing the infection produces a small significant rebound, but it is not known whether height and weight in children are impacted over the long term. Methods We investigated 295 school-age children followed in two cohorts, one treated (150) and one untreated (145), from 2004 for 3.7 years with 1105 child-years of observation. Follow-up intervals were 3 months for anthropometry measurements and 6 months for H. pylori status ascerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 12 publications
2
51
1
1
Order By: Relevance
“…Other prospective studies found no significant association between H pylori infection and ponderal growth ( Table 2). (Table 3) Limited evidence exists on the role of H pylori eradication on children's weight (13,26,32,47). Overall all these observational studies show evidence of some benefit for gains in body weight following H pylori eradication (13,26,32,47).…”
Section: Evidence From Longitudinal Studies (Table 2)mentioning
confidence: 95%
See 2 more Smart Citations
“…Other prospective studies found no significant association between H pylori infection and ponderal growth ( Table 2). (Table 3) Limited evidence exists on the role of H pylori eradication on children's weight (13,26,32,47). Overall all these observational studies show evidence of some benefit for gains in body weight following H pylori eradication (13,26,32,47).…”
Section: Evidence From Longitudinal Studies (Table 2)mentioning
confidence: 95%
“…Clearing H pylori infection was shown to have an increasingly significant effect on height up to 3.7 years of follow-up (26). This suggests a durable effect of clearing H pylori infection on increased height among school-age children treated for H pylori infection (26). A secondary analysis was performed for data obtained in the framework of a randomized controlled clinical trial of asymptomatic Native Alaska children of age 7 to 11 years, which assessed the role of H pylori treatment on iron deficiency.…”
Section: ããmentioning
confidence: 98%
See 1 more Smart Citation
“…Mera et al (2012) compared growth in communities where H. pylori-positive children received treatment to eliminate the infection to growth in communities where no intervention was offered. 81 At the end of an average follow-up of 3.7 y, children from the community that received treatment were 1.1 kg (95% CI: 0.64, 1.64) heavier on average than children from the non-intervention community, after adjusting for age, sex, father's education, number of siblings, cohort, follow-up time, H. pylori status, and the interaction between H. pylori status and followup time. Children from the community that received treatment were also 2.98 cm (95% CI: 2.04, 3.94) taller on average than children from the non-intervention community, after adjusting for age, sex, father's education, number of siblings, and presence of helminthes or protozoa in the stool.…”
Section: -81mentioning
confidence: 99%
“…pylori infection in children can produce gastric lesions that weaken or destroy the gastric acid barrier, 1 interfering with micronutrient absorption, appetite, metabolism, and related factors, and thereby inhibiting growth. [79][80][81] A small number of studies have investigated the impact of treatment to eliminate H. pylori infection on growth. 83 Differences in mean scores for height (cm), weight (kilograms), and BMI standard deviation scores (SDs) were estimated based on the 1990 UK growth reference charts.…”
Section: H Pylori Treatment and Effects On Growthmentioning
confidence: 99%